2011
DOI: 10.1212/wnl.0b013e318215286d
|View full text |Cite|
|
Sign up to set email alerts
|

Intrathecal EBV antibodies are part of the polyspecific immune response in multiple sclerosis

Abstract: Intrathecally produced anti-EBV antibodies are part of the polyspecific intrathecal immune response in CIS/MS and only rarely detectable in patients with CIS, both arguing against a direct CNS infection with EBV in patients with CIS/MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 25 publications
6
38
0
5
Order By: Relevance
“…There has been some epidemiologic evidence linking MS to other viral infections, especially to Epstein-Barr virus (EBV), however the underling mechanism is elusive (Otto et al 2011). About 90% of patients with MS show an elevated antibody index against one or more neurotropic viruses (Otto et al 2011), although this is possibly due as part of a polyspecific intrathecal humoral immune response (Otto et al 2011). Patients with HIV also show high intrathecal immunoactivation, up to the point that intrathecal immunoglobulin production can be measured even after years of effective HAART treatment and undetectable viral load (Eden et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There has been some epidemiologic evidence linking MS to other viral infections, especially to Epstein-Barr virus (EBV), however the underling mechanism is elusive (Otto et al 2011). About 90% of patients with MS show an elevated antibody index against one or more neurotropic viruses (Otto et al 2011), although this is possibly due as part of a polyspecific intrathecal humoral immune response (Otto et al 2011). Patients with HIV also show high intrathecal immunoactivation, up to the point that intrathecal immunoglobulin production can be measured even after years of effective HAART treatment and undetectable viral load (Eden et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests virus-specific responses within the CNS and thus indirectly suggests the presence of virus in this compartment [32]. This intrathecal response, however, has also been suggested to be part of the polyspecific response in MS [33]. Whether EBV is present in MS brains and particularly in the MS plaques is an important issue with conflicting reports in the literature.…”
Section: Is Ebv Present In Ms Brains?mentioning
confidence: 99%
“…AIs for antibodies against VZV were determined exactly as previously described by enzyme-linked immunosorbent assays (Enzygnost, Siemens Healthcare Diagnostics) [7]. A standard curve consisting of serial dilutions of standard human plasma (SHP, Siemens Healthcare Diagnostics) was included on each ELISA plate.…”
Section: Methodsmentioning
confidence: 99%
“…To characterize intrathecal antiviral immune responses in detail, but also for clinical differential diagnostic purposes, it appears desirable to clarify whether elevated antiviral AIs reflect virus-driven or polyspecific intrathecal immune responses. Others and we have previously shown that this can be achieved by calculating the fraction ( F S ) of the intrathecally-synthesized virus-specific immunoglobulin (Ig)G of the total intrathecally-synthesized IgG [5-7]. Nevertheless, the fraction of intrathecally-produced VZV-specific IgG of the total intrathecally-produced IgG ( F S anti-VZV) in patients with VZV reactivation and MS has hitherto not been compared.…”
Section: Introductionmentioning
confidence: 99%